2015
DOI: 10.1002/pbc.25594
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of intravenous melphalan combined with continuous infusion L-S,R -buthionine sulfoximine for children with recurrent neuroblastoma

Abstract: BSO/L-PAM has activity against recurrent high-risk NB. Exclusion of cephalosporin antibiotics in future clinical trials of BSO may diminish the potential for serious renal and CNS toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
(75 reference statements)
2
22
0
1
Order By: Relevance
“…Our determined IC50 values were similar to previously published values in similar cell lines18 and were also within the range of serum BSO levels seen in adults and children treated with BSO2146, suggesting that serum levels of BSO in our in vitro models are clinically achievable in patients with neural tumors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our determined IC50 values were similar to previously published values in similar cell lines18 and were also within the range of serum BSO levels seen in adults and children treated with BSO2146, suggesting that serum levels of BSO in our in vitro models are clinically achievable in patients with neural tumors.…”
Section: Discussionsupporting
confidence: 89%
“…BSO was also shown to be effective against neuroblastoma tumor cells, both alone and in combination with melphalan171819, and prior studies have reported that treatment of mice with human glioma and medulloblastoma xenograft tumors with BSO prior to melphalan resulted in increased survival20. Furthermore, a pilot clinical trial for treatment of children with recurrent neuroblastoma with BSO combined with melphalan demonstrated an 18% response rate21, suggesting a potential role for BSO in combination with other therapies for cancer patients.…”
mentioning
confidence: 98%
“…For example, melphalan, which is detoxified by GST, showed synergistic effects with BSO in a number of tumor lines (84). Moreover, BSO and melphalan proved generally well tolerated in phase I clinical trials involving advanced cancers (85,86), the one exception being in children with recurrent neuroblastoma (87). Of note, melphalan was shown to inhibit TrxR in vitro, although this is probably not the mechanism of action at physiological plasma concentrations, as melphalan is principally an alkylating agent (88).…”
Section: Treating Hiv/aids By Increasing Oxidative Stress: Results Frmentioning
confidence: 99%
“…A previous pilot study in 32 children with neuroblastoma utilized BSO (3 g/m 2 bolus and either 0.75 or 1 g/m 2 /hr 72 hr continuous infusion) followed by melphalan (15 mg/m 2 ) without stem cell support for one to four courses. Both BSO dose levels were tolerable . GSH depletion was demonstrated in peripheral blood monocytes.…”
Section: Introductionmentioning
confidence: 96%